Transformations of Regional Labor Markets in Ukraine in the Condition of War - Diakonenko О. І.; Kotenko Т. М. (Statistics of Ukraine, 2024)
The relevance of this research stems from the aggravating regional disproportionalities on the Ukrainian labor market. The current transformational shifts in the domestic labor market are accompanied by radical changes that feature chaotic nature and have destabilizing effects for the labor resource capacities and the compliance with labor-specific social standards and guarantees. The article’s objective is to explore the current transformations in the labor market across Ukrainian regions, caused by the impact of the Russian-Ukrainian war. An assessment of the transformation in workforce supply and demand in Ukrainian regions in 2014 and 2023 was made by a comparative analysis, statistical methods and data analysis. Spearmen’s rank correlation coefficient, coefficient of inequality of distribution, assessment of the significance of differences between two structures by JR criterion were used for an analysis of the transformations in regional and gender structures of the workforce supply and demand. Essential structural shifts in the regional structure of workforce supply were revealed, especially in the front-line areas, the city of Kyiv and Kyiv oblast. An asymmetry of distribution of the unemployed population was found to be increasing under the pressure of population replacement. An assessment of the gender structure of workforce supply allowed for the following grouping of regions: the first group of 18 regions with the structures close to the average Ukrainian estimate; the second group covering four oblasts with small differences from the average Ukrainian estimate and a limited scope of labor uses; the third group covering three oblasts with essential differences from the average Ukrainian estimate and a narrow labor market capacity due to the proximity of the front line. The main steps to minimize the adverse impact of the regional disproportionality of the labor market were substantiated: creating and revitalizing jobs in territorial communities of Ukraine that are safe for living, to supply unemployed population with jobs in the formal sector of the economy and to encourage migrants’ coming back from abroad; elaborating schemes and implementing tools for regulation of spatial mobility and movement of workforce between labor-deficient and labor-surplus labor markets; stimulating retraining and training for the occupations expected to enjoy demand in the short- and long-term perspective.